Strategi Mitigasi Outstanding dalam Skema Pembiayaan BankZiska melalui Penerapan Al-Qardhul Hasan - Prasetianti, Isnaeni Gelda; Fathurohman SW, Oman (State of Islamic Institute Langsa, 2024)
The increasing outstanding in the al-Qardhul Hasan-based BankZiska financing scheme reflects the gap between the ideals of an interest-free, penalty-free, and solidarity-based program and the reality of potential abuse by partners, such as failure to repay. BankZiska, as a program based on zakat, infaq, and sadaqah funds, aims to help small communities, especially MSME players, free themselves from loan sharks and ribawi practices. The program provides soft loans without additional fees, which are designed in accordance with sharia principles and DSN-MUI fatwas. This study identifies the risk mitigation strategies applied by BankZiska to maintain the sustainability of the financing scheme. A literature study-based qualitative approach is used to analyze the effectiveness of the joint liability system, periodic monitoring, and intensive mentoring. The findings show that these strategies effectively reduce the risk of default, increase the ethos of economic independence, and build community awareness of Islamic economics. The program also has a positive impact on partner empowerment through entrepreneurship training and Islamic financial education. BankZiska is not only a financial solution, but also part of economic da'wah to encourage people's independence.